2016
DOI: 10.1007/s00586-016-4922-5
|View full text |Cite
|
Sign up to set email alerts
|

The Norwegian Cervical Arthroplasty Trial (NORCAT): 2-year clinical outcome after single-level cervical arthroplasty versus fusion—a prospective, single-blinded, randomized, controlled multicenter study

Abstract: Purpose Standard surgical treatment for symptomatic cervical disc disease has been discectomy and fusion, but the use of arthroplasty, designed to preserve motion, has increased, and most studies report clinical outcome in its favor. Few of these trials, however, blinded the patients. We, therefore, conducted the Norwegian Cervical Arthroplasty Trial, and present 2-year clinical outcome after arthroplasty or fusion. Methods This multicenter trial included 136 patients with single-level cervical disc disease. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 47 publications
0
54
0
1
Order By: Relevance
“…3,8,11,20,21,25,27 The only double-blinded RCT, however, displayed higher NDI scores and more arm pain in the arthroplasty group after 2 years. 34 In our study, there were fewer reoperations in the fusion group than in the ADR group and the incidence of nonunion was low. Our results contradict other large RCTs with a 5-year follow-up, 3,8 i.e., they reported a higher frequency of secondary surgery in the control group compared with the ADR group, mostly because of nonunion.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…3,8,11,20,21,25,27 The only double-blinded RCT, however, displayed higher NDI scores and more arm pain in the arthroplasty group after 2 years. 34 In our study, there were fewer reoperations in the fusion group than in the ADR group and the incidence of nonunion was low. Our results contradict other large RCTs with a 5-year follow-up, 3,8 i.e., they reported a higher frequency of secondary surgery in the control group compared with the ADR group, mostly because of nonunion.…”
Section: Discussionmentioning
confidence: 44%
“…The results of that study were in favor of fusion surgery. 34 Complications after ADR surgery occur, including spontaneous fusion and loosening. 6,14,33,38 None of the larger open-label randomized controlled trials had long-term follow-up with MRI.…”
mentioning
confidence: 99%
“…is the most commonly used procedure at the neurosurgical department of Oslo University Hospital. This strategy is supported by a recent randomised controlled trial at our hospital that found no clinical benefits of disc prosthesis [22]. All operations will be carried out by experienced and qualified neurosurgeons.…”
Section: Decompression Surgerymentioning
confidence: 98%
“…Further, the disc prosthesis (cervical arthroplasty) has been proposed to improve results. A recently published Norwegian multicentre trial did not favour discectomy and disc prosthesis compared with the traditional discectomy and fusion [22]. The trial included patients with one-level radiculopathy (C6 or C7) primarily caused by spondylosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation